Multifocal intraoral ductal ectasia with metaplasia and focal epithelial proliferation: a case report - Abe, Shigehiro; Yokomizo, Naoko; Asano, Masatake; Mishimagi, Takashi; Hyodo, Katsuya; Kobayashi, Yutaka; admin (Journal of the Pakistan Medical Association, 2022)
Ductal ectasia with metaplasia and focal epithelial proliferation in the oral cavity does not correspond to any existing salivary gland lesion. A 72-year-old man presented with a mass in the buccal mucosa, which was excised and initially diagnosed as a cystadenoma. An upper lip mass on the right side, which developed later, was also excised. The lesions were histologically similar, and since they were multifocal and in non-contiguous and independent sites with multiple dilated cystic structures that did not destroy the lobar architecture, the final diagnosis was confirmed as ductal ectasia with metaplasia and focal epithelial proliferation. This condition may mimic various neoplastic lesions. Keywords: Salivary ducts, salivary gland disease, salivary gland neoplasm, mucocele, metaplasia.